Digital Learning: Differentiated teaching models using ICTs to students with vision problems – Good practices: I add by playing from 1 to 10 - Lykou, Paraskevi; Chaidi, Irene; Driga, Anna Maria (Brazilian Journal of Science, 2023)
The idea of inclusion encourages an inclusive, open-door school. By adapting formal instruction to standard instruction that is acceptable for everyone while taking into account the requirements, quirks, skills, interests, and experiences of each student, the use of ICTs aids in this direction. One such group is the visually challenged, whose inclusion in general education classes is made possible with the use of ICTs. In the current study, a method of individualized education in the field of mathematics is developed and put into practice, allowing all students-visually impaired or not-to master the mathematical operation of adding to the first ten at their own speed and time. Results show that differentiated instruction improves students’ ability to understand mathematical operations: ADDITION from 1 to 10.